Regulating the regulator: Numb acts upstream of p53 to control mammary stem and progenitor cell - Faraldo, Marisa M. (J Cell Biol, 2015)
In this issue, Tosoni et al. (2015. J. Cell Biol. http://dx.doi.org/10.1083/jcb.201505037) report that cell fate determinant and tumor suppressor Numb imposes asymmetric cell divisions in mammary stem cells by regulating p53. Numb thereby restricts mammary stem cell expansion and controls the proliferation and lineage-specific characteristics of their progeny.